Pengaruh Keputusan Pembelian, Kepuasan Pelanggan Terhadap Minat Beli Ulang Pada Shopeefood Di Kota Malang (Studi Kasus Pada Mahasiswa Feb Universitas Islam Malang Angkatan 2021) - Moh. Isnaini Ramanda Putra; Muhammad Ridwan Basalamah; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract This study aims to analyze the influence of purchase decisions and customer satisfaction on repurchase intention for ShopeeFood services in Malang City, with a case study on students of the Faculty of Economics and Business, Islamic University of Malang, class of 2021. The research employs a quantitative approach, collecting data through questionnaires distributed to 89 respondents. Data analysis was conducted using multiple linear regression to examine the relationship between the independent variables (purchase decisions and customer satisfaction) and the dependent variable (repurchase intention). The results indicate that both simultaneously and partially, purchase decisions and customer satisfaction have a positive and significant effect on repurchase intention. The coefficient of determination (R2) of 0.751 suggests that 75% of the variation in repurchase intention can be explained by these two independent variables, while the remaining 25% is influenced by other factors not examined in this study. These findings imply that enhancing purchase decisions and customer satisfaction can foster consumer loyalty towards ShopeeFood services. Keywords: Purchasel, Delcision, Customelr Satisfaction, Rapurchasel Intelntion, Shoppelelfood.